SEXUAL EDUCATION TO IMPROVE SEXUAL INFORMATION LITERACY IN CHILDREN 9-12 YEARS - Azni Nurul Fauzia; Syamsu Yusuf LN; Nandang Budiman (Universitas Pendidikan Indonesia, 2022)
Sexual information literacy is a set of skills that children need to process sexual information normatively. When the child starts to enter a period of sexual development in a more mature direction, a sense of attraction and curiosity leads the child to search for information. When children feel a sexual topic is too taboo to be discussed with adults, accessing information through the internet cannot longer be controlled. Inaccurate sources of information can set children as victims as well as perpetrators of inappropriate sexual behavior according to applicable values and norms. One of the efforts that can be given in assisting healthy sexual development is through sexual education as an effort to increase sexual information literacy. Sexual education is considered effective in forming healthy sexual behavior for children and adolescents in the future.